The risk of secondary sex ratio imbalance and increased monozygotic twinning after blastocyst transfer: data from the Japan Environment and Children's Study - Hiromitsu Hattori; Akane Kitamura; Fumiaki Takahashi; Norio Kobayashi; Akiko Sato; Naoko Miyauchi; Hidekazu Nishigori; Satoshi Mizuno; Kasumi Sakurai; Mami Ishikuro; Taku Obara; Nozomi Tatsuta; et al. (BMC, 2019)
Abstract Background Some studies have suggested that blastocyst transfer is associated with i) imbalance in the secondary sex ratio (SSR) (which favors male offspring), ii) increased incidence of monozygotic twins (MZT). In contrast, others have not found these changes. In this study, we evaluated the association between blastocyst transfer and SSR and MZT, considering potential parental confounders. Methods The Japan Environment and Children's Study is a large, nationwide longitudinal birth cohort study funded by the Ministry of the Environment of Japan. We used this large dataset, including 103,099 pregnancies, to further investigate the association between blastocyst transfer, SSR and MZT, using spontaneously conceived pregnancies, non-assisted reproductive technology (non-ART) treatment (intrauterine insemination and ovulation induction with timed intercourse) and cleavage stage embryo transfer for comparison. We evaluated the association with each group, the SSR, and the frequency of MZT, calculating the adjusted odds ratio (AOR) using multivariable logistic regression analyses, adjusting for potential parental confounders such as basic health and socioeconomic status. Results For each group (spontaneous conception vs. non-ART treatment vs. cleavage stage embryo transfer vs. blastocyst transfer), the percentages of males were 51.3% vs 50.7% vs 48.9% vs 53.4% and the monozygotic twinning rates per pregnancy were 0.27% vs 0.11% vs 0.27% vs 0.99% respectively. Multivariate logistic regression analyses indicated that blastocyst transfer was significantly associated with a higher SSR and higher incidence of MZT than the other three groups (SSR: AOR 1.095, 95% CI1.001-1.198; MZT: AOR 4.229, 95% CI 2.614-6.684). Conclusions There are significant relationships between blastocyst transfer and SSR imbalance and a higher occurrence of MZT.